(untitled) (Pakistan Journal of Science, 2025)
Worker’s well-being has been a priority for organizations in the digital work era. But many established measures of well-being don’t truly reflect employees’ needs, particularly those with disabilities or access needs. Measures of well-being generally focus on productivity, stress, or engagement. They miss out on other important dimensions such as physical accessibility, cognitive aids, emotional support, and social inclusion. As a result, the efficacy of well-being initiatives is limited, and the long-term sustainability of practices in the human resource business is enhanced. The proposed conceptual framework of accessibility, disability inclusion, and sustainable HRM can measure the well-being of the employees. This study will be a mixed-method approach. This is critical to make sense of the current scenario of organizational definition and ways of measurement of well-being. The study will show that inclusive well-being metrics positively impact employees’ motivation and intentions to leave the organization. As a result, they bolster an organization’s resilience and sustainability processes. The study enhances theoretical and practical insights by offering workable suggestions on HR practices and workforce inclusion of disabilities within the organization. The findings reveal how vital it has become to move beyond traditional measures to combat this pandemic.